Couples of childbearing age do not participate in the family planning program in Salekoe Village, Palopo City - Asmawati; Mayanti, Andi; Juliani (International Journal of Public Health Excellence (IJPHE), 2023)
A couple of childbearing age (PUS) is a married couple who still has the potential to have children or is usually marked by the time when menopause has not yet arrived (menstruation has stopped for the wife). Family planning is a method that helps individuals or married couples to regulate the interval between pregnancies and determine the number of children in the family. This research was conducted to obtain information regarding the reasons why couples of childbearing age do not participate in family planning programs. This research is descriptive in nature. The sample used was 212 EFA taken according to the specified criteria. Data collection was carried out by filling out a questionnaire, then the data was processed and analyzed using the frequency distribution formula. The research results showed that the highest reason for PUS not participating in the Family Planning program was wanting to have children immediately, 68 PUS (24.82%) while the lowest was not being suitable for using family planning, namely 3 PUS (1.1%). From the results of this research, it is recommended to increase education, especially about the types of contraceptives, side effects and complications.